Increasing rates of methamphetamine/amphetamine-involved overdose hospitalizations in Washington State, 2010–2017. (December 2021) - Njuguna, Henry; Gong, Jian; Hutchinson, Katie; Ndiaye, Mamadou; Sabel, Jennifer; Wasserman, Cathy
Highlights: Methamphetamine/amphetamine-involved overdose hospitalizations are increasing. Rate of increase highest in patients aged ≥55 years. More than a third of patients had a polysubstance overdose. Opioid was the most frequent drug class involved in polysubstance overdoses. Abstract: Background and aims: In the United States, overdose deaths resulting from methamphetamine and other amphetamine-type stimulants (METH/AMPH) have been increasing. We describe rates and characterize patients hospitalized after a METH/AMPH-involved overdose in Washington State, to guide prevention and control measures. Design, setting, participants: We conducted a trend analysis of hospitalized Washington State residents aged ≥15 years who received a METH/AMPH-involved overdose diagnosis in Washington's civilian hospitals and reported in the Comprehensive Hospital Abstract Reporting System. Measurements: We used Joinpoint regression analysis to study trends in rates of hospitalized patients who received a METH/AMPH-involved overdose diagnosis during 2010–2017. We used 2016–2017 data to describe characteristics of patients with nonfatal and fatal outcomes and used chi-square test (for categorical variables) and Wilcoxon rank-sum test (for continuous variables) to compare characteristics of patients by outcome. Findings: During 2010–2017, 3587 patients were hospitalized and received a METH/AMPH-involved overdose diagnosis. The age-adjusted rate for METH/AMPH-involved overdose hospitalization increased from 6.3/100, 000 persons in 2010 to 8.5/100, 000 persons in 2017. Patients aged ≥55 years had the greatest increase in rate of overdose hospitalizations. Among these patients, 86% also had a substance use disorder diagnosis involving substances other than METH/AMPH, and 35% experienced a polysubstance overdose. Conclusions: We observed increasing rates of METH/AMPH-involved overdose hospitalizations in Washington State, particularly among persons aged ≥55 years. Approximately a third of patients also experienced a polysubstance overdose, which can be considered when designing interventions to address increasing rates of overdose hospitalizations in Washington State.